Effect of dexmedetomidine on attenuation of hemodynamic response to intubation, skin incision, and sternotomy in coronary artery bypass graft patients: A double-blind randomized control trial - Manoj Kamal; Deepa Agarwal; Geeta Singariya; Kamlesh Kumari; Bharat Paliwal; Shobha Ujwal (Journal of Anaesthesiology Clinical Pharmacology, 2020)
Background and Aims: Coronary artery bypass grafting (CABG) surgery involves various noxious stimuli resulting in stress response, which in turn increases the risk of perioperative myocardial ischemia. The present study was conducted to evaluate the effect of dexmedetomidine on the attenuation of hemodynamic response to intubation, skin incision, and sternotomy in CABG surgery. Material and Methods: Sixty patients were randomized into two groups of 30 each. Group D patients received dexmedetomidine 1 μg/kg as loading dose over 10 min, followed by continuous infusion of 0.5 μg/kg/h. In group P, normal saline was infused as loading and maintenance dose at similar rate. Hemodynamic parameters, total induction dose of thiopentone, and adverse effects were recorded. Statistical analysis was performed using SPSS version 20.0. Chi-square test and ANNOVA test were used and P < 0.05 was considered significant. Results: The percentage increase in heart rate was significantly lesser in group D than group P after intubation (7.04% v/s 15.08%), skin incision (5.91% v/s 10.11%), and sternotomy (5.33% v/s 11.65%). Similarly increase in systolic, diastolic, and mean blood pressure were significantly lesser in group D than group P after intubation, skin incision, and sternotomy. There was a significant reduction of mean total of thiopentone in group D in comparison to group P. (1.16 mg/kg v/s 2.44 mg/kg) (P< 0.001). Conclusion: Dexmedetomidine resulted in significant attenuation of hemodynamic response to intubation, skin incision, and sternotomy in CABG surgery without significant adverse effects. It also significantly reduced the dose of thiopentone required for induction.